PENGARUH MEDITASI TERHADAP TEKANAN DARAH PADA ORANG HIPERTENSI - Bagus Adi Marthayoga (Coping: Community of Publishing in Nursing, 2015)
Hypertension is a core problem that can cause of death for non-infection category disease. Besides that, hypertension also is a major cause of heart failure and stroke. One of hypertension causes is the increase stimulation of sympatic neuron stress response excessively. Meditation is a manner to reduce stress response with relaxation technique. This research aim to find out the influence of meditation for  the  blood pressure people’s with hypertension in bungbungan-banjarangkan-klungkung. This research using quasy experience ( pretest-posttest ) design on 20 respondents that chosen by purposive sampling technique, and it divided into a control group and intervention group. Based on the results of paired t-test ( p < 0.05 ) on intervention group obtained 0,022systole and 0,047diastole blood pressure, it means there is a difference blood pressure on intervention group after given meditation, however, on control group the systole and diastole are 0.47 , 0,216 it means there is not difference blood pressure on control group. Analysis the differences in blood pressure on both of the group using independent t-test ( p < 0.05 ) with the value 0,088 on the systole and 0,194 for the diastole, that means there is no difference blood pressure in the systole and diastole of control and intervention group.